ChemInform Abstract: Synthesis, Structure, and Electronic Structure Calculation of a New Centrosymmetric Borate Pb2O[BO2(OH)] Based on Anion‐Centered OPb4 Tetrahedra. Issue 34 (4th August 2016) - Sun, Feng; Wang, Li; Stoumpos, Constantinos C.
Abstract: The new title compound is prepared by hydrothermal reaction of a 1:2:5 molar mixture of Pb(NO3 )2, SrCO3, and H3 BO3 in 1 M KOH (autoclave, 180 °C, 1 d, 40% yield).